Ukrainian agrarian capitalism of the Hetmanate: «track effect» and economic peripherality (second half of the 17th century) - S.Z. Moshenskyi (Економіка, управління та адміністрування)
In the development of economic systems, the so-called «track effect» (path dependence) is often revealed – the dependence of the economy and the main trends of its growth from the historical past. The dominance of economic and institutional traditions does not allow innovations to enter the economic space. This effect becomes especially noticeable in periods when the social system and the economy are being reformatted, and when there is a chance to choose a new trajectory of economic growth. One of these periods was the wars of Bohdan Khmelnytskyi, as a result of which emerged the Ukrainian national state – the Hetmanate. Although it almost immediately found itself dependent on the Moscow tsar, the economy of the Hetmanate had at least half a century to realize this chance for a new path of economic development. Unfortunately, this attempt was unsuccessful for the agrarian oligarchic capitalism of the Hetmanate. Even during its rise (under hetmans Samoilovich and Mazepa), this economy remained very simple. The grain boom has already passed, and wheat has been replaced by a new export product – beef cattle, which were driven to Western Europe. Primitive production of potash and vodka (mainly for export), iron and glass was developed. Taxes remained the main source of filling the budget of the Hetmanate, and renting tax collection was then considered the most profitable business. All these businesses were held in the hands of the Cossack foreman – a small oligarchic stratum of the society of the Hetmanate. The goal of personal enrichment was put first, so corruption, lawlessness, business capture from smaller entrepreneurs became commonplace. The new leaders of the Hetmanate’s economy were essentially no different from the Polish land magnates against whom their ancestors fought during Khmelnytskyi’s time. This is how the «track effect» manifested itself, and during these half-century the peripherality of the Ukrainian economy not only did not decrease, but became even greater compared to the era of the great grain boom of the late 16th and early 17th centuries.